Kopi, Trend Minuman Kekinian Dengan Banyak Manfaat Komponen Bioaktif - Jufrinaldi, Jufrinaldi; Indrawati, Wiwik; Nurmaida, Nurmaida (Jurnal Riset, Inovasi, Teknologi & Terapan, 2024)
Coffee is a widely enjoyed beverage in Indonesia and around the world, holding a significant role as a key commodity in Indonesia's plantation sector. This beverage is popular not only for its distinctive flavor but also for its various health benefits. This article reviews several main bioactive components in coffee, including caffeine, chlorogenic acid, ferulic acid, and caffeic acid, as well as the potential health benefits of each. Caffeine is known as a stimulant that can enhance alertness, reduce drowsiness, and acts as a potential antioxidant. Chlorogenic acid functions as an anti-inflammatory, antihypertensive, antidiabetic, and anti-obesity agent, helping to reduce the risk of cardiovascular diseases. Ferulic acid has strong antioxidant effects and is used as a diabetes therapy due to its ability to reduce oxidative stress, while caffeic acid is known for its anticancer, antioxidant, and antibacterial activities, supporting the prevention of atherosclerosis and cardiovascular diseases. This article also discusses the mechanisms of action for each bioactive component within the body, particularly on the nervous system, lipid metabolism, and antioxidant activity. Through this review, coffee is understood not only as a refreshing beverage but also as a potential agent in the therapy and prevention of various chronic diseases.